COMPUTER PROCEDURES OF THE SOFTWARE COMPLEX FOR DETERMINING THE TENSION OF THE THREAD SUPPLY PROCESS ON CIRCULAR KNITTING MACHINES - SHCHERBAN, VOLODYMYR; KOLISKO, OKSANA; KOLISKO, MARJANA; KIRICHENKO, ANTON; SHCHERBAN, YURYJ (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Determining the intensity of the thread feed process on a circular knitting machine for elastic weaves allows you to initially determine the technological loads that will occur during the interaction of the thread with the guides and working bodies depending on the type of raw material, curvature of guide surfaces, thread feed rate. The tension is changed due to the interaction of the threads with the guides of the circular knitting machine for elastic weaves of large and small curvature, tensioning devices. The development of procedures for the computer determination of thread tension on a circular knitting machine for elastic weaves should be based on the use of object-oriented programming languages. Determining the tension and changes in relative tension in the refueling zones of a circular knitting machine for elastic weaves, taking into account the specifics of the design of the thread feed system, will improve the technology of processing raw materials on a circular knitting machine for elastic weaves.The improvement of technological processes of thread processing on a circular knitting machine for elastic weaves should be based on complex studies of the process of interaction of threads with combined tensioning devices, working guide surfaces of large and small curvature of the feed system. Theoretical dependences for determining the tension will allow to obtain mathematical software used in computer software to calculate the tension and change the relative tension in the refueling zones of circular knitting machine for elastic weaves, reduce the percentage of thread breakage, improve the quality of knitted fabric.You can reduce the tension of the thread feeding process and reduce the number of thread breaks on a circular knitting machine for elastic weaves by using quality raw materials and optimizing the interaction of threads with tensioning devices on a circular knitting machine for elastic weaves, where there is interaction of threads with surfaces large and small curvature. Thread tension relationships are systems of transcendental equations that require numerical methods to solve.
Keywords: computer procedures; software package; recursion algorithm; thread feed; circular knitting machines